TRAJECTORIES OF CHINESE-MUSLIM STUDENTS’ CULTURAL IDENTITY AND THEIR CHALLENGES IN UIN MALANG - Rosi, Rois Imron; Yousif, Ahmad F (Ulul Albab: Jurnal Studi Islam, 2024)
Understanding cultural identity among students is a critical yet often underexplored dimension of educational research, particularly in multicultural societies. This study investigates the identity formation processes of Chinese-Muslim students in Malang, Indonesia, emphasizing the urgency of fostering cultural awareness and tolerance in educational settings. The research highlights how identity construction directly influences students’ sense of belonging and participation in society. Furthermore, it underscores the importance of cultural sensitivity for educators who engage with diverse learners. Employing a qualitative methodology, this study explores the lived experiences of five Chinese-Muslim students in navigating their cultural identities. Findings reveal that all participants belong to the Hui ethnic group but tend to self-identify as "pure Chinese," distancing themselves from their Hui-Muslim heritage. Despite physical similarities to the Han majority in China, these students experience marginalization in Indonesia due to their Chinese features, often feeling like cultural outsiders. In the academic context, their learning behaviors are shaped by cultural norms that emphasize passivity and individual effort, contrasting with the collaborative learning style more prevalent among their Indonesian peers. This creates challenges in group-based educational activities, although self motivation and strong parental support act as key enablers. By illuminating these identity dynamics, this study contributes to the broader discourse on inclusive education and intercultural understanding. The findings call for urgent pedagogical strategies that accommodate cultural diversity, enhance student engagement, and promote mutual respect in increasingly pluralistic classrooms.